Designing a hybrid type photoelectrochromic device with dual coloring modes for realizing ultrafast response/high optical contrast self-powered smart windows. (December 2021) - Cheng, Chao-Yuan; Chiang, Yu-Jou; Yu, Hsin-Fu; Hsiao, Li-Yin; Yeh, Chia-Lin; Chang, Ling-Yu; Ho, Kuo-Chuan; Yeh, Min-Hsin
Abstract: The self-powered smart window is a promising wire-free system to integrate on the energy-saving building due to its independent and sustainable operations without an external power source. Solar-driven photoelectrochromic devices (PECDs), which derived from the hybridization of dye-sensitized solar cells (DSSCs) and electrochromic devices (ECDs), are potential systems to realize the convenient self-powered smart window. To further boosting up the optical contrast and minimizing the response time, in this study, a brand new hybrid type photoelectrochromic device (H-PECD) composed with a new architecture of independently covered photoelectrode with electrochromic conducting polymeric layer and a novel counter electrode (CE) with bifunctional electrochemical layer is proposed in the first time. Compared to traditional combined-type PECDs (C-PECD), the electrochromic and the photoactive layers are independently integrated on the photoelectrode to overcome the limitation of electrochromic material selection. By taking this advantage, a conducting polymer of PEDOT-MeOH with high coloration efficiency can be introduced to serve as the electrochromic layer for further enhancing the optical performance of H-PECD. Furthermore, a highly transparent electrochemical layer serves as bifunctional CE for not only facilitating the I3 - reduction reaction for accelerating the bleaching rate, but also contributes additional optical contrast of 3% under coloring process. By comparing with another classic configuration of separated type PECD (S-PECD), the coloring and bleaching time of H-PECD can be shortened within 5 s under maximum transmittance change at 600 nm for 31.7% since the photovoltaic performance and photo-coloration efficiency (PhCE) is improved by integrating with bifunctional CE. By taking advantage of H-PECD, duel-coloring modes of high optical contrast and ultrafast response can be achieved by controlling the operating processes. This research is a substantial advancement toward the practical application of PECDs and self-powered smart windows. Graphical Abstract: ga1 Highlights: A brand new design of a hybrid type photoelectrochromic device (H-PECD) was proposed for the first time. Independently covered photoelectrode solved the bottleneck of electrochromic material selection. A bifunctional counter electrode possesses optical complementary and electrocatalytic ability. Duel-coloring modes of high optical contrast and ultrafast response for H-PECD can be achieved. H-PECD provided a new strategy to realize the self-powered smart windows for green building.